Spatial Analysis of Existing Public Open Space for Evacuation Area During Secondary Earthquake; A Case Study: Sukahaji Village, Bandung - Sagala, Saut; Saraswati, Sari (Forum Geografi, 2013)
Population living in highly densed settlements in urban area is considered vulnerable to earthquake risk due to limited space exists in the area. To reduce population risks to aftershock earthquake in highly dense settlements, this paper applied simple simulation based on supply-demand concepts in order to understand carrying capacity of current open space for people to evacuate. The case study takes place in one of the most densed populated areas in Bandung City under aftershock earthquake.. The research integrates multi-sources of data: sattelite image, building footprint and GPS field survey to produce detailed landuse. The results show that open spaces that exist in the study area is not able to contain all residents when an aftershock occurs. Finally, this paper recommends some strategies that are necessary to reduce the risks in highly densed urban areas.